Effect of ambulatory oxygen on quality of life for patients with fibrotic lung disease (AmbOx): a prospective, open-label, mixed-method, crossover randomised controlled trial. Issue 10 (October 2018) - Visca, Dina; Mori, Letizia; Tsipouri, Vicky; Fleming, Sharon; Firouzi, Ashi; Bonini, Matteo; Pavitt, Matthew J; Alfieri, Veronica; Canu, Sara; Bonifazi, Martina; Boccabella, Cristina; De Lauretis, Angelo; et al.
Summary: Background: In fibrotic interstitial lung diseases, exertional breathlessness is strongly linked to health-related quality of life (HRQOL). Breathlessness is often associated with oxygen desaturation, but few data about the use of ambulatory oxygen in patients with fibrotic interstitial lung disease are available. We aimed to assess the effects of ambulatory oxygen on HRQOL in patients with interstitial lung disease with isolated exertional hypoxia. Methods: AmbOx was a prospective, open-label, mixed-method, crossover randomised controlled clinical trial done at three centres for interstitial lung disease in the UK. Eligible patients were aged 18 years or older, had fibrotic interstitial lung disease, were not hypoxic at rest but had a fall in transcutaneous arterial oxygen saturation to 88% or less on a screening visit 6-min walk test (6MWT), and had self-reported stable respiratory symptoms in the previous 2 weeks. Participants were randomly assigned (1:1) to either oxygen treatment or no oxygen treatment for 2 weeks, followed by crossover for another 2 weeks. Randomisation was by a computer-generated sequence of treatments randomly permuted in blocks of constant size (fixed size of ten). The primary outcome, which was assessed by intention to treat, was the change in total score on the King's Brief Interstitial Lung Disease questionnaire (K-BILD) after 2 weeks on oxygen compared with 2 weeks of no treatment. General linear models with treatment sequence as a fixed effect were used for analysis. Patient views were explored through semi-structured topic-guided interviews in a subgroup of participants. This study was registered withClinicalTrials.gov, numberNCT02286063, and is closed to new participants with all follow-up completed. Findings: Between Sept 10, 2014, and Oct 5, 2016, 84 patients were randomly assigned, 41 randomised to ambulatory oxygen first and 43 to no oxygen. 76 participants completed the trial. Compared with no oxygen, ambulatory oxygen was associated with significant improvements in total K-BILD scores (mean 55·5 [SD 13·8] on oxygen vs 51·8 [13·6] on no oxygen, mean difference adjusted for order of treatment 3·7 [95% CI 1·8 to 5·6]; p<0·0001), and scores in breathlessness and activity (mean difference 8·6 [95% CI 4·7 to 12·5]; p<0·0001) and chest symptoms (7·6 [1·9 to 13·2]; p=0·009) subdomains. However, the effect on the psychological subdomain was not significant (2·4 [–0·6 to 5·5]; p=0·12). The most common adverse events were upper respiratory tract infections (three in the oxygen group and one in the no-treatment group). Five serious adverse events, including two deaths (one in each group) occurred, but none were considered to be related to treatment. Interpretation: Ambulatory oxygen seemed to be associated with improved HRQOL in patients with interstitial lung disease with isolated exertional hypoxia and could be an effective intervention in this patient group, who have few therapeutic options. However, further studies are needed to confirm this finding. Funding: UK National Institute for Health Research.